Penerapan Model Pembelajaran Project Based Learning (PjBL) untuk Meningkatkan Motivasi Belajar Pendidikan Pancasila Siswa Kelas V UPTD SDN 85 Parepare - Ritha Tuken; Musfirah Musfirah; M. Wahyu Ramadhan (MASALIQ, 2026)
The low learning motivation of fifth-grade students in Pancasila Education at UPTD SDN 85 Parepare indicates the need to implement a learning model capable of increasing student engagement in the learning process. This study aimed to improve the quality of the learning process and students’ learning motivation through the implementation of the Project-Based Learning (PjBL) model. The study employed a classroom action research design with a qualitative approach conducted in two cycles, each comprising planning, implementation, observation, and reflection stages. The research participants consisted of one teacher and 34 fifth-grade students, including 15 male and 19 female students. Data were collected through observation, questionnaires, and documentation and were subsequently analyzed through data condensation, data display, and conclusion drawing. The results showed that, in Cycle I, teacher activities, student activities, and students’ learning motivation were in the fair category. Following improvements in Cycle II, teacher and student activities increased to the good category, while students’ learning motivation reached the very good category. This improvement was indicated by increased enthusiasm, active engagement, group collaboration, and students’ enjoyment during the learning process. Thus, the implementation of the Project-Based Learning model was effective in improving the learning process and students’ learning motivation in Pancasila Education in the fifth grade at UPTD SDN 85 Parepare. These findings imply that PjBL can be used as an alternative learning model to create more active, collaborative, and enjoyable Pancasila Education learning.